2006
DOI: 10.2113/gsemg.15.3-4.35
|View full text |Cite
|
Sign up to set email alerts
|

Chemostratigraphy at the Brunswick No. 6 Volcanic-Sediment-Hosted Massive Sulfide Deposit, New Brunswick: Resolving Geometry from Drill Core in Deformed Felsic Volcanic Rocks

Abstract: Diamond-drill hole DDH-B357, located 1.5 km north of the Brunswick No. 6 Zn-PbCu-Ag volcanic-sediment-hosted massive sulfide (VSHMS) deposit, intersects three exhalative horizons within variably altered felsic volcanic rocks of the Nepisiguit Falls and Flat Landing Brook formations. These three petrographically indistinguishable iron formation intervals (Fe 2 O 3 T ≥ 21.4 wt.%) likely represent cogenetic hydrothermal sedimentary units because they display a common geochemical signature: Fe 2 O 3 T = 42.9 ± 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…On the other hand, previous S isotope studies have been carried out on deposits of the Iberian Pyrite Belt, Bathurst Mining Camp and Finlayson Lake District (Wolverine) [81][82][83][84]. These are considered a transitional type named VSHMS deposit, which occurs between typical VMS and SEDEX deposits [84][85][86][87]. The studies showed that δ 34 S values in the sulfides of these deposits are roughly positive with minor negative values.…”
Section: Source Of Sulfurmentioning
confidence: 99%
“…On the other hand, previous S isotope studies have been carried out on deposits of the Iberian Pyrite Belt, Bathurst Mining Camp and Finlayson Lake District (Wolverine) [81][82][83][84]. These are considered a transitional type named VSHMS deposit, which occurs between typical VMS and SEDEX deposits [84][85][86][87]. The studies showed that δ 34 S values in the sulfides of these deposits are roughly positive with minor negative values.…”
Section: Source Of Sulfurmentioning
confidence: 99%